Generative Code Modeling with Graphs - Brockschmidt, Marc; Allamanis, Miltos; Gaunt, Alex; Polozov, Alex (7th International Conference on Learning Representations, 2019)
Generative models for source code are an interesting structured prediction problem, requiring to reason about both hard syntactic and semantic constraints as well as about natural, likely programs. We present a novel model for this problem that uses a graph to represent the intermediate state of the generated output. The generative procedure interleaves grammar-driven expansion steps with graph augmentation and neural message passing steps. An experimental evaluation shows that our new model can generate semantically meaningful expressions, outperforming a range of strong baselines. Get the code on GitHub >